2019
DOI: 10.1002/anie.201813960
|View full text |Cite
|
Sign up to set email alerts
|

Merging Photochemistry with Electrochemistry: Functional‐Group Tolerant Electrochemical Amination of C(sp3)−H Bonds

Abstract: Direct amination of C(sp3)−H bonds is of broad interest in the realm of C−H functionalization because of the prevalence of nitrogen heterocycles and amines in pharmaceuticals and natural products. Reported here is a combined electrochemical/photochemical method for dehydrogenative C(sp3)−H/N−H coupling that exhibits good reactivity with both sp2 and sp3 N−H bonds. The results show how use of iodide as an electrochemical mediator, in combination with light‐induced cleavage of intermediate N−I bonds, enables the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
114
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(126 citation statements)
references
References 84 publications
3
114
0
9
Order By: Relevance
“…Given the substantial benefits of these two broad paradigms, processes that combine photocatalysis and electrocatalysis could be especially attractive.N evertheless,t he merger of electro-and photocatalysis in organic chemistry has rarely been achieved. [15] Meanwhile, Grätzel and Hu have shown that the photoelectric effect can be utilized for the coupling of electron-rich arenes with azoles. Meanwhile,S cheffold achieved the nucleophilic acylation of electron-deficient olefins using vitamin B 12 as areductive electrophotocatalyst.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the substantial benefits of these two broad paradigms, processes that combine photocatalysis and electrocatalysis could be especially attractive.N evertheless,t he merger of electro-and photocatalysis in organic chemistry has rarely been achieved. [15] Meanwhile, Grätzel and Hu have shown that the photoelectric effect can be utilized for the coupling of electron-rich arenes with azoles. Meanwhile,S cheffold achieved the nucleophilic acylation of electron-deficient olefins using vitamin B 12 as areductive electrophotocatalyst.…”
mentioning
confidence: 99%
“…Fore xample,X ud emonstrated the alkylation of arenes with organotrifluoroborates using photoredox catalysis coupled with anodic re-oxidation, [14] and Stahl developed aH ofmann-Lçffler-Freytagtype CÀHa mination reaction using electrochemical iodination paired with photochemical homolysis. [15] Meanwhile, Grätzel and Hu have shown that the photoelectric effect can be utilized for the coupling of electron-rich arenes with azoles. [16] We envisioned the merger of light and electrical energy via the design of new single-component "electrophotocatalysts".…”
mentioning
confidence: 99%
“…Such potentials are less positive than the redox potentials of electron-rich arenes and other functional groups and thus the mild conditions allow excellent redox chemoselectivity. Stahl demonstrated 52 that previously reported electron transfer/proton transfer/electron transfer (ET-PT-ET), 53 proton-coupled electron transfer (PCET) 54 and bromide-mediated electrochemical HLF reactions 55 all failed to convert 47 into product 48, instead yielding a complex mixture of products.…”
Section: Decoupled Photoelectrochemistry (Dpec)mentioning
confidence: 94%
“…Stahl reported a Hofmann-Löffler-Freytag-type (HLF) amination of C(sp 3 )-H bonds under dPEC. 52 (Figure 11). Near-UV photochemistry cleaved the N-I bond while anodic potential oxidized iodide to molecular iodine (the cathodic reaction involved reduction of protons to hydrogen).…”
Section: Decoupled Photoelectrochemistry (Dpec)mentioning
confidence: 99%
“…随着光氧化还原反应的发展, 将光促 进的氧化还原反应与传统过渡金属参与的偶联反应 [43] 相结合, 已经产生了许多令人耳目一新的催化反应模 式, 极大地拓宽了光促反应的应用范围. 同时, 电催化 的模式已在有机合成反应中取得了很多突破 [44] , 不仅 可以在温和条件下产生自由基中间体 [45,46] , 也能调控 过渡金属的氧化态 [47,48] , 有利于开发新型过渡金属催 化反应机制, 在温和条件下实现惰性碳氢键的活化. 此 外, 电氧化还原催化模式还能够避免使用当量的氧化 剂或还原剂, 为发展原子经济性的化学转化过程提供 了另一个强大的平台, 在甲烷均相转化中具有很大的 发展潜力 [49] .…”
Section: 在建立金属催化剂和配体的相关反应模型基础上unclassified